2007
DOI: 10.1175/jcli4134.1
|View full text |Cite
|
Sign up to set email alerts
|

Australian Rainfall and Surface Temperature Variations Associated with the Southern Hemisphere Annular Mode

Abstract: Daily variations in Australian rainfall and surface temperature associated with the Southern Hemisphere annular mode (SAM) are documented using observations for the period 1979-2005. The high index polarity of the SAM is characterized by a poleward contraction of the midlatitude westerlies. During winter, the high index polarity of the SAM is associated with decreased daily rainfall over southeast and southwest Australia, but during summer it is associated with increased daily rainfall on the southern east coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
439
4
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 497 publications
(493 citation statements)
references
References 37 publications
(41 reference statements)
31
439
4
4
Order By: Relevance
“…For example, during two of the three extended dry periods shown here the SAM is persistently positive. Note that while SAM is not shown to be positive during the Federation Drought (∼ 1895-1902) there is some question over the validity of the index used to represent SAM during the earlier part of the record (Ho et al, 2012); further, the influence of the SAM is very seasonally dependent for Australian rainfall (Hendon et al, 2007), with opposite effects on rainfall in summer versus winter, which may be negated when analyzing annual rainfall. As shown in Figure 6 the DMI was predominantly positive during the dry period that occurred between ∼ 1925-1945, contributing to the synchronicity observed during this period, particularly between Australia and South Africa.…”
Section: Synchronicity In Dry Spells Across the Southern Hemisphere Smentioning
confidence: 99%
“…For example, during two of the three extended dry periods shown here the SAM is persistently positive. Note that while SAM is not shown to be positive during the Federation Drought (∼ 1895-1902) there is some question over the validity of the index used to represent SAM during the earlier part of the record (Ho et al, 2012); further, the influence of the SAM is very seasonally dependent for Australian rainfall (Hendon et al, 2007), with opposite effects on rainfall in summer versus winter, which may be negated when analyzing annual rainfall. As shown in Figure 6 the DMI was predominantly positive during the dry period that occurred between ∼ 1925-1945, contributing to the synchronicity observed during this period, particularly between Australia and South Africa.…”
Section: Synchronicity In Dry Spells Across the Southern Hemisphere Smentioning
confidence: 99%
“…Frederiksen et al, 1999;Hendon et al, 2007). To demonstrate the decreasing rainfall trend completely and exactly, trends were assessed monthly.…”
Section: Selection Of the Analysis Periodmentioning
confidence: 99%
“…Maximum rainfall occurred along the southeastern and eastern coast, as well as the northern and southwestern coast, decreasing far inland. Previous studies demonstrated that Australian spring rainfall is influenced by many factors, such as the El Niño-Southern Oscillation (ENSO) (e.g., McBride and Nicholls 1983;Ropelewski and Halpert 1987;Nicholls et al 1996;Chiew et al 1998;Taschetto and England 2009), the Indian Ocean dipole (e.g., Saji et al 1999;Ashok et al 2003;Ummenhofer et al 2011), and the Antarctic Oscillation or southern annular mode (e.g., Gong and Wang 1999;Thompson and Wallace 2000;Marshall 2003;Hendon et al 2007). For example, studies find that Australian rainfall tends to be below average during El Niño events and above average during La Niña events, especially across the eastern two-thirds of the Australian continent during austral spring (e.g., Allan 1988;Wang and Hendon 2007).…”
Section: Introductionmentioning
confidence: 99%